The Effect of Edmodo-Based Blended Learning on Students’ Achievement - Jesi Jecsen Pongkendek; Evy Nurvitasari; Ardi Firmansyah (J-PEK (Jurnal Pembelajaran Kimia), 2021)
Blended learning is a mixed learning model that combines online and face-to-face learning that utilizes a website or application that can be accessed with a smartphone, laptop, or computer connected to the internet network. Blended learning is an alternative learning model applied during the Covid-19 pandemic. This study aims to determine the effect of the Edmodo-based blended learning model on student learning outcomes. This type of research is pre-experimental with one group pretest-posttest design. The research was conducted at SMAN 1 Kurik with Class XI MIPA 1, which consisted of 26 students as the research sample. Research data was obtained in learning outcomes data conducted at the beginning and end of learning. Student learning outcomes data were analyzed parametrically with paired sample t-test. Based on the results of the study, it was obtained that students' learning completeness was 85%, N-Gain was 0.56 (medium category), and t-count was 20.79 (t-count > t-table). Through this research, it can be concluded that there is an influence of the Edmodo-based blended learning model on the chemistry learning outcomes of students in class XI MIPA 1 SMAN 1 Kurik.